Administration of recombinant bovine somatotropin prior to fixed-time artificial insemination and the effects on fertility, embryo, and fetal size in beef heifers. (20th April 2018) - Oosthuizen, Nicola; Fontes, Pedro L P; Henry, Darren D; Ciriaco, Francine M; Sanford, Carla D; Canal, Luara B; de Moraes, Gentil V; DiLorenzo, Nicolas; Currin, John F; Clark, Sherrie; Whittier, William D; Mercadante, Vitor R G; et al.
Abstract: Our objectives were to determine the effects of the administration of recombinant bovine somatotropin (bST ) at the initiation of a fixed-time AI (TAI ) protocol on concentrations of plasma IGF-1, follicle diameter, embryo/fetal size, and pregnancy rates in replacement beef heifers. Four hundred and fourteen Angus-based beef heifers were enrolled in a completely randomized design at 4 locations from January to July of 2016. All heifers were exposed to the 7-d CO-Synch + controlled internal drug release (CIDR ) protocol where they received a 100-µg injection of GnRH and a CIDR insert on day −9, 25 mg of PGF2α at CIDR removal on day −2, followed by a 100-µg injection of GnRH and TAI 54 ± 2 h later on day 0. Within location, all heifers were randomly assigned to 1 of 2 treatments: 1) heifers that received 650 mg of bST on day −9 (BST; n = 191); or 2) heifers that did not receive bST on day −9 (CONTROL; n = 223). Blood samples were collected on day −9, 0, 28, and 60 to determine the plasma concentrations of IGF-1. Follicle diameter was determined on day −2 and 0 by transrectal ultrasonography. Pregnancy was diagnosed via transrectal ultrasonography on day 28 or 35, and again at least 30 d after the end of the breeding season. Embryo morphometry was assessed by measuring crown-to-rump length (CRL ) on day 28, and fetal size was assessed by measuring crown-to-nose-length (CNL ) on day 60. Concentrations of plasma IGF-1 did not differ between treatments on day −9 ( P = 0.924), 28 ( P = 0.075), and 60 ( P = 0.792); however, concentrations of plasma IGF-1 were greater ( P < 0.001) in BST-treated heifers at TAI (372.4 ± 16.6 vs. 193.7 ± 16.6 ng/ml). No differences ( P = 0.191) were detected for follicle diameter between CONTROL and BST treatments on day −2 or 0. Pregnancy rates to TAI (PR/AI) were greater ( P = 0.028) for CONTROL compared to BST heifers (42.5 ± 4.0 vs. 29.9 ± 4.1%). No differences ( P = 0.536) in CRL were observed on day 28 between CONTROL and BST heifers. In addition, no difference ( P = 0.890) was observed for CNL between CONTROL and BST treatments. Final pregnancy rates did not differ ( P = 0.699) between treatments. The administration of bST to beef heifers at the initiation of a TAI protocol increased plasma concentrations of IGF-1 at TAI; however, failed to enhance follicle diameter, embryo/fetal size, and reduced PR/AI.